PENGARUH BAURAN PEMASARAN JASA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JAMINAN KESEHATAN NASIONAL DI KLINIK KOTA TASIKMALAYA - Suhartini, Titin; Saryomo, Saryomo (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
The purpose of this study was to determine the effect of marketing mix and service quality on JKN customer satisfaction at the Tasikmalaya City Clinic, this study uses descriptive and verification methods, data analysis uses descriptive analysis and multiple regression. The results revealed 1) marketing mix influenced JKN customer satisfaction with a value of 0.589, 2) service quality affected JKN customer satisfaction with a value of 0.669, and 3) marketing mix and service quality jointly influenced JKN customer satisfaction with a value of 0.684. Conclusion, there is an effect both directly and jointly the marketing mix and service quality on customer satisfaction National Health Insurance in the Tasikmalaya City clinic.Â Keywords: Marketing Mix, Service Quality and Customer Satisfaction